A Planar Decanuclear Cobalt(II) Phosphonate. Issue 15 (22nd April 2014) - Sahoo, Dipankar; Metre, Ramesh K.; Kroener, Wolfgang; Gieb, Klaus; Müller, Paul; Chandrasekhar, Vadapalli
Abstract: A decanuclear cobalt(II) phosphonate, [Co10 2, 3, 5, 6‐(Me)4 C6 HCH2 PO3 8 2, 3, 5, 6‐(Me)4 C6 HCH2 PO3 H4 Cl6 ]· 6Et3 NH· 10 n ‐hexane· 16H2 O (1 ) with a planar arrangement of the Co II ions is described. This compound shows slow relaxation of its dynamic magnetization. Abstract : A decanuclear cobalt(II) phosphonate, [Co10 2, 3, 5, 6‐(Me)4 C6 HCH2 PO3 8 2, 3, 5, 6‐(Me)4 C6 HCH2 PO3 H4 Cl6 ]· 6Et3 NH· 10 n ‐hexane· 16H2 O with a planar arrangement of the Co II ions is described. This compound shows slow relaxation of its dynamic magnetization.